Pemilihan Kepala Desa di Desa Air Joman Kabupaten Asahan Tahun 2007 - KURNIAWAN, HERI (Politeia: Jurnal Ilmu Politik, 2011)
In realizing political independence at local level, otonomi desa (autonomy countryside) has been realized in Indonesia. One of materialization evidence it is execution of head election countryside directly. This Study discusses about process of election Kepala Desa (head election countryside) that has took place in the countryside Air Joman, Kabupaten Asahan (Sub-province Asahan). Data is got by using observation method, interview, and document study. Technique of data analysis is descriptive method that is describing phenomenon base on data and information. This study finding indicates that basically the phase of election Kepala Desa Air Joman has run acording to the rule. Nevertheless, in election Kepala Desa Air Joman is ex-isted some problems. The first problem is at procces of elector identification. The second prob-lem is at procces of screening the candidate. The third problem is collision in campaign. This Phenomenon indicates that principle countryside political democracy development still requires repair from process facet and the technique.Keywords: Local election, political participation, democratization.